Economic use of plants is key to their naturalization success - van Kleunen, Mark; Xu, Xinyi; Yang, Qiang; Maurel, Noëlie; Zhang, Zhijie; Dawson, Wayne; Essl, Franz; Kreft, Holger; Pergl, Jan; Pyšek, Petr; Weigelt, Patrick; Moser, Dietmar; et al. (Nature communications, 2020)
Humans cultivate thousands of economic plants (i.e. plants with economic value) outside their native ranges. To analyze how this contributes to naturalization success, we combine global databases on economic uses and naturalization success of the world’s seed plants. Here we show that naturalization likelihood is 18 times higher for economic than non-economic plants. Naturalization success is highest for plants grown as animal food or for environmental uses (e.g. ornamentals), and increases with number of uses. Taxa from the Northern Hemisphere are disproportionately over-represented among economic plants, and economic plants from Asia have the greatest naturalization success. In regional naturalized floras, the percentage of economic plants exceeds the global percentage and increases towards the equator. Phylogenetic patterns in the naturalized flora partly result from phylogenetic patterns in the plants we cultivate. Our study illustrates that accounting for the intentional introduction of economic plants is key to unravelling drivers of plant naturalization. Understanding why certain alien species become naturalized can shed light on biological invasion patterns. In this global analysis on thousands of taxa, van Kleunen and colleagues show that plant species of economic use are more likely to become naturalized, and that this underlies geographic patterns and phylogenetic signals in naturalization